2022
DOI: 10.1155/2022/5955052
|View full text |Cite
|
Sign up to set email alerts
|

Six MicroRNA Prognostic Models for Overall Survival of Lung Adenocarcinoma

Abstract: Objective. The purpose of this study is to screen for microRNAs (miRNAs) associated with the prognosis of lung adenocarcinoma (LUAD) and to explore its prognosis and effects on the tumor microenvironment in patients with LUAD. Methods. Gene expression data, miRNA expression data, and clinical data for two different databases, TCGA-LUAD and CPTAC-3 LUAD, were downloaded from the GDC database. The miRNA prognosis of LUAD was filtered by the Cox proportional hazard model and the Least Absolute Shrinkage and Selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In addition, we uncovered a prognosis-relevant exosome miRNA, hsa-miR-1293, in the immune microenvironment of PDAC. Prior research has indicated that hsa-miR-1293 is overexpressed in hepatocellular cancer [48] and serves as an unfavorable prognostic factor for lung cancer [17] . On the contrary, hsa-miR-1293 was a tumor suppressive factor for renal cancer [20] , [22] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we uncovered a prognosis-relevant exosome miRNA, hsa-miR-1293, in the immune microenvironment of PDAC. Prior research has indicated that hsa-miR-1293 is overexpressed in hepatocellular cancer [48] and serves as an unfavorable prognostic factor for lung cancer [17] . On the contrary, hsa-miR-1293 was a tumor suppressive factor for renal cancer [20] , [22] .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are highly conserved noncoding RNAs that primarily silence gene expression by binding to the 3' untranslated regions (3'UTRs) of target genes. Extensive research has demonstrated that miRNAs orchestrate a variety of biological processes, including differentiation, proliferation, migration, invasion, metabolism, and apoptosis [21]. For instance, miR-584-3p has been shown to inhibit invasion in clear cell renal cell carcinoma by downregulating ROCK-1 [22] and to regulate migration in human thyroid cancer cells [23].…”
Section: Discussionmentioning
confidence: 99%